Respuesta :

(x-h)²+(y-k)²=r²

when the center is (h,k) and the radius is r

given

(-1,2) and r=3

(x-(-1))²+(y-2)²=3²

(x+1)²+(y-2)²=3²

C is answer

Answer:

Option C is correct.

Step-by-step explanation:

We have been given the center of circle: (-1,2) and radius of length 3.

The general equation of circle is:

[tex](x-h)^2+(y-k)^2=r^2[/tex]

Here, h= -1, k=2 and r=3

h and k is the center of circle

On substituting the values in the formula we get:

[tex](x-(-1))^2+(y-2)^2=3^2[/tex]

[tex]\Rightarrow (x+1)^2+(y-2)^2=9[/tex]

Therefore, Option C is correct.